2012
DOI: 10.1021/cb300351x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Quorum Sensing in the Pathogen Acinetobacter baumannii Using Non-native N-Acyl Homoserine Lactones

Abstract: Many bacterial pathogens use quorum sensing (QS) to control virulence. As a result, the development of methods to intercept QS has attracted significant interest as a potential anti-infective therapy. Acinetobacter baumannii has emerged as a pan-drug resistant pathogen and displays a remarkable ability to persist in hospital settings despite desiccation and antimicrobial treatment. Recent studies have shown that A. baumannii QS mutants have limited motility and fail to form mature biofilms – these phenotypes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 67 publications
0
131
0
1
Order By: Relevance
“…However, there were no significant differences in the phase variation frequency in either direction between opaque and translucent variants in the abaI mutant compared to the wild type (data not shown). In addition, a quorum sensing signal produced in an AbaI-dependent manner is 3-OH C 12 -homoserine lactone (3-OH C 12 -HSL) (31,32). The ability of synthetic 10 M 3-OH C 12 -HSL to stimulate phase variation was examined, but no significant differences were observed compared to growth in LB without 3-OH C 12 -HSL ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, there were no significant differences in the phase variation frequency in either direction between opaque and translucent variants in the abaI mutant compared to the wild type (data not shown). In addition, a quorum sensing signal produced in an AbaI-dependent manner is 3-OH C 12 -homoserine lactone (3-OH C 12 -HSL) (31,32). The ability of synthetic 10 M 3-OH C 12 -HSL to stimulate phase variation was examined, but no significant differences were observed compared to growth in LB without 3-OH C 12 -HSL ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Even though phenotypically distinct, all forms of motility described for A. baumannii have been shown to depend on synthesis of the polyamine 1,3-diaminopropane (26). Surface motility of A. baumannii was further shown to be controlled by blue light sensing (28) and quorum sensing (24,29) and to depend on iron availability (30,31).…”
mentioning
confidence: 99%
“…When the number of bacteria reaches a critical level, AHL becomes an effective sensing signal that prompts the production of a large number of intercellular adhesins in the polysaccharides, and the biofilm is formed by embedding the micro-colonies. [23] However, Stacy et al [24] demonstrated that Acinetobacter baumannii used non-N-…”
Section: Biofilm Sensingmentioning
confidence: 99%